SARS-Cov-2 spike induces intestinal barrier dysfunction through the interaction between CEACAM5 and Galectin-9 - Luo, Yingshu; Zhang, Zhenling; Ren, Jiangnan; Dou, Chunxu; Wen, Jiancheng; Yang, Yang; Li, Xiaofeng; Yan, Zhixiang; Han, Yanzhi (Frontiers in Immunology, 2024)
Background: Carcinoembryonic antigen-related cell adhesion molecule 5 (CEACAM5), as a typical tumor marker, has been found to exert immunomodulatory effects in many diseases. We previously reported the clinical and molecular evidences supporting that SARS-Cov-2 infected the gastrointestinal (GI) tract and found a reduction of CEACAM5 in COVID-19 patients' feces which associated with gut dysbiosis. Yet the role of CEACAM5 in GI infection is ill-defined.Methods: Mice models were established through intraperitoneally injecting with recombinant viral spike-Fc to mimic the intestinal inflammation. We collected duodenum, jejunum, ileum and colon samples after 6h, 2 days, 4 days and 7 days of spike-Fc or control-Fc injection to perform proteomic analysis. Blood was collected from healthy donors and peripheral blood mononuclear cells (PBMC) were separated by density gradient centrifugation, then CD4+ T cells were isolated with magnetic beads and co-cultured with Caco-2 cells. Results: In addition to intestinal CEACAM5, the expression of tight junction and the percent of CD4+ T lymphocytes were significantly decreased in spike-Fc group compared to control (p < 0.05), accompanied with increased level of inflammatory factors. The KEGG analysis revealed differentially expressed proteins were mainly enriched in the coronavirus disease (COVID-19), tight junction, focal adhesion, adherens junction and PI3K-Akt signaling pathway. Protein-protein interaction (PPI) network analysis identified the interaction between CEACAM5 and Galectin-9 that was also verified by molecular docking and co-IP assay. We further confirmed a reduction of CEACAM5 in SARS-CoV-2 spike stimulated enterocytes could promote the expression of Galectin-9 protein in CD4+T cells. Then it gave rise to the increasing release of inflammatory factors and increased apoptosis of CD4+T cells by inhibition of PI3K/AKT/mTOR pathway. Ultimately intestinal barrier dysfunction happened. Conclusions: Our results indicated that CEACAM5 overexpression and Galectin-9 knockdown played a protective role in intestinal barrier injury upon spike-Fc stimulation. Collectively, our findings identified firstly that SARS-CoV-2 spike induced intestinal barrier dysfunction through the interaction between CEACAM5 and Galectin-9. The result provides potential therapeutic targets in intestinal barrier dysfunction for treating severe COVID patients.